Extreme Delta Brush in Anti-NMDAR Encephalitis Correlates With Poor Functional Outcome and Death - Nathoo, Nabeela; Anderson, Dustin; Jirsch, Jeffrey (Frontiers in Neurology, 2021)
Objective: To characterize EEG findings in anti-NMDAR encephalitis patients looking for the proportion of EEGs that were abnormal, presence of extreme delta brush (EDB), and to relate EEG findings to clinical outcomes (Glasgow Outcome Scale (GOS) at 6 months, need for ICU admission, and death). Methods: This retrospective cohort single center study included patients with anti-NMDAR encephalitis who had ≥1 EEGs obtained from 2014 to 2021. EEGs were retrospectively analyzed by 2 reviewers. Clinical outcomes of interest were extracted through hospital and clinic chart review. Results: Twenty-one patients with anti-NMDAR encephalitis were included. Sixty-four EEGs were analyzed. Four EEGs (6.3%) were within normal limits. Focal or generalized slowing (without EDB) was seen on 44 EEGs (68.8%). EDB was seen on 16 EEGs (25.0%) in 9 of 21 patients (42.9%). The presence of EDB was significantly associated with need for ICU admission (p = 0.02), poorer outcome at 6 months as per the GOS (p = 0.002), and with death (p=0.02). EDB was present on ≥1 EEG of every patient who died. Conclusions: The presence of EDB on EEG in anti-NMDAR encephalitis patients is associated with increased need for ICU admission, worse functional outcomes at 6 months, and risk of death.